Changes in anthocyanin profile, color, and antioxidant capacity of hawthorn wine (Crataegus pinnatifida) during storage by pretreatments. (September 2018) - Liu, Suwen; Zhang, Xuan; You, Lu; Guo, Zhaoyuan; Chang, Xuedong
Abstract: The effects of microwave and heating pretreatments on the content and composition of anthocyanins, ascorbic acid content, and total phenol content, along with the color density and antioxidant capacity of "Xinglongzirou" hawthorn wine during storage were investigated. Ten anthocyanins were identified in the hawthorn fruit using HPLC-ESI/MS 2 analysis. After fermentation, only six anthocyanins were detected. Pretreatment significantly increased the total amount of anthocyanin in the stored hawthorn wine (p < 0.05). The total phenol content decreased during storage and the total anthocyanin content showed a similar trend. The content of oligocyanogen in microwave- and heat-pretreated samples was higher than that in the control, especially the microwave-treated group, in which the amount of oligocyanogen was higher than that in the control group by 24.6% after 180 days (p < 0.05). During storage, the color tonality of hawthorn wine increased. Three methods (DPPH scavenging ability, ORACFL assay, and T-AOC assay) were employed to evaluate the antioxidant capacity of the hawthorn wine during storage. The antioxidant capacities of the microwave- and heat-pretreated groups were higher than those of the control group. Highlights: Ten anthocyanins were identified using HPLC-ESI/MS 2 analysis. Microwave and heating pretreatments increased the extraction of phenolic. After storage, the anthocyanin monomers significantly decreased. The pretreatments maintaining higher levels of phenolic at least for 30 days. During storage, hawthorn wine had a stable color density.